Parir e sangrar em corpo soberano: os usos e sentidos da Ginecologia Natural no circuito das doulas - Bezerra, Stephanie Bittencourt (2024)
This work investigates, through ethnographic research, the doula circuit in Rio Grande do Norte, taking as an empirical focus the activities promoted and/or attended by those who are associated with the alternative aspect of the Movement for the Humanization of Childbirth. This circuit is currently made up of meetings that have disseminated the ideas of the so-called Natural Gynecology — a sociocultural expression emerging in Latin America in the last two decades that, assuming a critical stance in the face of the presence of a colonial epistemology in hegemonic assistance to women's health, has become popularized through “knowledge exchange” circles, therapeutic experiences and workshops, promoting a particular symbolic system in light of its demands. The research sought to understand how doulas have incorporated the ideas of Natural Gynecology into their narratives and practices, what points of contact this movement has with the Humanization of Childbirth and its own ideas, and what this implies in the construction of the individual trajectories of the interlocutors.This text also highlights the contribution of these agents in the construction of other meanings around bodies and their events, such as gestation, birth and menstruation cycle. This work has particularly appropriated the theoretical and methodological elaborations of Urban Anthropology, Feminist Anthropology and some formulations around the gender axis, other epistemologies and decoloniality produced, above all, by women in the Global South.